Spatiotemporal regulation of autophagy during Caenorhabditis elegans aging - Chang, Jessica T; Kumsta, Caroline; Hellman, Andrew B; Adams, Linnea M; Hansen, Malene (eLife, 2017)
Autophagy has been linked to longevity in many species, but the underlying mechanisms are unclear. Using a GFP-tagged and a new tandem-tagged Atg8/LGG-1 reporter, we quantified autophagic vesicles and performed autophagic flux assays in multiple tissues of wild-type Caenorhabditis elegans and long-lived daf-2/insulin/IGF-1 and glp-1/Notch mutants throughout adulthood. Our data are consistent with an age-related decline in autophagic activity in the intestine, body-wall muscle, pharynx, and neurons of wild-type animals. In contrast, daf-2 and glp-1 mutants displayed unique age- and tissue-specific changes in autophagic activity, indicating that the two longevity paradigms have distinct effects on autophagy during aging. Although autophagy appeared active in the intestine of both long-lived mutants, inhibition of intestinal autophagy significantly abrogated lifespan extension only in glp-1 mutants. Collectively, our data suggest that autophagic activity normally decreases with age in C. elegans, whereas daf-2 and glp-1 long-lived mutants regulate autophagy in distinct spatiotemporal-specific manners to extend lifespan.
Keywords: autophagy; Atg8/LC3; tissue-specificity; aging; daf-2; glp-1